2019
DOI: 10.3390/medicina55090603
|View full text |Cite
|
Sign up to set email alerts
|

Naturopathy as a Model of Prevention-Oriented, Patient-Centered Primary Care: A Disruptive Innovation in Health Care

Abstract: Background and Objective: The concept of a “disruptive innovation,” recently extended to health care, refers to an emerging technology that represents a new market force combined with a new value system, that eventually displaces some, or all, of the current leading “stakeholders, products and strategic alliances.” Naturopathy is a distinct system of traditional and complementary medicine recognized by the World Health Organization (WHO), emerging as a model of primary care. The objective here is to describe N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 76 publications
(100 reference statements)
0
6
0
1
Order By: Relevance
“…We are of the view that public health can turn to Naturopathy as well for some answers in crisis such as COVID-19 [6]. We have also noted that both public health and Naturopathic principles are analogous [6] hence, policy makers can as well turn to Naturopathy for remedies to the escalating cases of public health issues [7] Though we found that there are challenges in the practice of Naturopathy from Stacy's narratives and the quantitative study (Fig. 20), we are of the view that these challenges stem partly from mistrust between Conventional and Naturopathic practitioners.…”
Section: Discussionmentioning
confidence: 98%
“…We are of the view that public health can turn to Naturopathy as well for some answers in crisis such as COVID-19 [6]. We have also noted that both public health and Naturopathic principles are analogous [6] hence, policy makers can as well turn to Naturopathy for remedies to the escalating cases of public health issues [7] Though we found that there are challenges in the practice of Naturopathy from Stacy's narratives and the quantitative study (Fig. 20), we are of the view that these challenges stem partly from mistrust between Conventional and Naturopathic practitioners.…”
Section: Discussionmentioning
confidence: 98%
“…Naturopathic medicine has great potential to address primary healthcare needs. 15 In addition to treating acute and chronic conditions, NDs engage in health promotion and prevention of disease. 60 Naturopathic medicine has the potential to become a "disruptive innovation" in health care due to its ability to address primary healthcare needs, particularly chronic diseases, such as depression and diabetes, without the use of expensive pharmaceutical and surgical interventions, while also providing highly qualified professionals to bolster the primary care workforce.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Research suggests that NDs, as primary HCPs, may be well situated to help integrate complementary or alternative (CAM) therapies into conventional primary care, creating a more holistic model that can better address health through prevention and management of chronic disease. 13,[15][16][17][18][19] In light of the unique challenges faced by this region and in support of the integration of the naturopathic profession, there are many considerations that need to be taken into account to enact effective change in the healthcare sector. These considerations include past efforts, on going colonialism, the unique needs of northern Ontario's populations, and the ND scope of practice.…”
Section: Introductionmentioning
confidence: 99%
“…There is a myriad of disruptive technologies and innovations that have revolutionized health care and continued to do so over many years [7,20,21], which are out of the scope of this review that focuses on disruptive innovation in the field of laboratory medicine, as detailed below.…”
Section: Disruptive Innovation In Health Carementioning
confidence: 99%